2017
DOI: 10.1097/aln.0000000000001528
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Induces Apoptosis and Suppresses Tumor Growth in Human Hepatocellular Carcinoma Cells In Vitro and in a Xenograft Model In Vivo

Abstract: Background Recent epidemiologic studies have focused on the potential beneficial effects of regional anesthetics, and the differences in cancer prognosis may be the result of anesthetics on cancer biologic behavior. However, the function and underlying mechanisms of lidocaine in hepatocellular carcinoma both in vitro and in vivo have been poorly studied. Methods Human HepG2 cells were treated with lidocaine. Cell viability, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
124
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 56 publications
10
124
0
5
Order By: Relevance
“…It is supposed that by functional modifications or combination with other drugs, lidocaine might achieve greater anticancer effects. The combination of lidocaine with cisplatin has been proposed as a novel treatment option for hepatocellular carcinoma (19). In this study, we found that lidocaine significantly inhibited the proliferation of AGS and HGC-27 cells at an effective concentration of 10 μM within 72 h with important clinical significance, whilst ropivacaine had an inhibitory effect on gastric cells at 1 mM, which is a much higher dose that can only be achieved by local infiltration clinically.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It is supposed that by functional modifications or combination with other drugs, lidocaine might achieve greater anticancer effects. The combination of lidocaine with cisplatin has been proposed as a novel treatment option for hepatocellular carcinoma (19). In this study, we found that lidocaine significantly inhibited the proliferation of AGS and HGC-27 cells at an effective concentration of 10 μM within 72 h with important clinical significance, whilst ropivacaine had an inhibitory effect on gastric cells at 1 mM, which is a much higher dose that can only be achieved by local infiltration clinically.…”
Section: Discussionmentioning
confidence: 66%
“…breast, lung, liver and thyroid) (15)(16)(17)(18). It has been reported that lidocaine inhibited the growth of HepG2 cells in a dose-dependent and time-dependent manner, arrested cells in the G 0 /G 1 phase of the cell cycle and induced apoptosis (19). Lidocaine at 1 mM was also shown to induce cell-cycle arrest in colon carcinoma cell lines in vitro (20).…”
Section: Significantly Inhibited the Proliferation Of Ags And Hg-27 Cmentioning
confidence: 99%
“…Ropivacaine, lidocaine and bupivacaine are amide-linked local anesthetics and act on neuron cells via blocking voltage-gated sodium-channel (VGSC) and subsequent depolarization suppression [8]. They have been shown to exhibit anti-proliferative, antimetastatic and pro-apoptotic potential on cell culture and xenograft mouse models in a variety of cancers [9][10][11][12][13]. In addition, local anesthetics preferentially target cancer stem cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…The growing evidence of local anaesthetics inhibiting cancer cell growth seems promising, though limited [11]. At the tissue level, administration of a certain amount of local anaesthetics topical or local has shown to have a direct inhibitory effect on the action of epidermal growth factor receptor (EGFR) which is a potential target for anti-proliferation in cancer cells [12,13]. Evidence also shows that ropivacaine and lidocaine hinder cancer cells growth, invasion, migration and enhance apoptosis of lung cancer cells [14 -18].…”
Section: Introductionmentioning
confidence: 99%